The water remembers : my Indigenous family's fight to save a river and a way of life - Cordalis, Amy Bowers (Little, Brown and Company, 2025)
"For the members of a Northern California tribe, salmon are the lifeblood of the people--a vital source of food, income, and cultural identity. When a catastrophic fish kill devastates the river, Amy Bowers Cordalis is propelled into action, reigniting her family's 170-year battle against the U.S. government. In a ... blend of memoir and history, Cordalis propels readers through generations of her family's struggle, where she learns that the fight for survival is not only about fishing--it's about protecting a way of life and the right of a species and river to exist. Her great-uncle's landmark Supreme Court case reaffirming her Nation's rights to land, water, fish, and sovereignty, her great-grandmother's defiant resistance during the Salmon Wars, and her family's ongoing battles against government overreach shape the deep commitment to justice that drives Cordalis forward. When the source of the fish kill is revealed, Cordalis steps up as General Counsel for the Yurok Tribe to hold powerful corporate interests accountable, and to spearhead the largest river restoration project in history. The Water Remembers is a testament to the enduring power of Indigenous knowledge, family legacy, and the determination to ensure that future generations remember what it means to live in balance with the earth"--